Intensifying cropping sequences in the US Central Great Plains: an in silico analysis of a sorghum–wheat sequence - Marziotte, Lucia; Carcedo, Ana J. P.; Rodriguez, Daniel; Mayor, Laura; Prasad, P. V. Vara; Ciampitti, Ignacio A. (Frontiers in Plant Science, 2025)
IntroductionIn the Central Plains of the United States (US), wheat (Triticum aestivum L.) is predominantly grown as a monocrop, limiting profits, and compromising environmental sustainability. In the context of recent reports on crop yield stagnation and the increased frequency and intensity of climate extremes, this study aims to i) evaluate the economic feasibility of double cropping sorghum (Sorghum bicolor L.) with winter wheat; ii) identify regional environmental drivers for yield; and iii) map the spatial distribution of the most profitable crop sequences.MethodsThe APSIM classic model was used to simulate the baseline wheat and sorghum monocrops and the diversified crop sequence (sorghum-wheat) over 30 years of climatology (1990 to 2020), across 194 sites in Kansas, United States. Each site was characterized in APSIM, with the predominant soil type and current farming crop management practices. Using terciles of historical input costs for all crop sequences we calculated three cost scenarios low, intermediate, and high. A fuzzy-C means algorithm was used to classify regions based on crop sequences’ profits, resulting in four clusters.Results and discussionResults included two regions where sorghum-wheat was more profitable than the monocrops i.e., one with lower profits (S+W lower), and a second one with higher profits (S+W higher); a third cluster where wheat monocrop was most profitable (W), and lastly one cluster showing no difference between the sorghum-wheat sequence and the wheat monocrop (S+W or W). Principal component analyses were used to identify environmental drivers of profit in each cluster. Results showed that the profitability of the sorghum-wheat sequence was higher in counties in the south-east and south-central of Kansas. Wheat monocrops were the most profitable option for counties of the west and central regions. Counties from the north-east of the state showed similar patterns amongst scenarios. These results highlight potential avenues for diversifying and intensifying the current wheat monocrop sequence while maintaining or increasing profitability. Lastly, this study delineates a map in Kansas with areas where it would be more profitable for farmers to expand their rotations by adding a second crop per year.